Rough Set Theory Approach for Classifying Multimedia Data - Abdul Rahman, Prof. Dr. Mohd Nordin (Springer, 2011)
The huge of multimedia data requires for efficient data classification and organization on proving effective multimedia data manipulation.Those valuable data most be captured and stored for potential purposes.One of the main problems in Multimedia Information System (MIS) is the management of multimedia data